Pembuatan Susu Alternatif Kombinasi Singkong (Manihot esculenta) dan Kacang Koro Pedang (Canavalia ensiformis) - Jamilah, Wardatul; Hanizar, Evi; Danuji, Sarwo (Biocaster : Jurnal Kajian Biologi, 2025)
This study aims to develop alternative dairy products based on local ingredients, namely cassava (Manihot esculenta) and koro sword beans (Canavalia ensiformis) as a solution for individuals with lactose intolerance, as well as to support the use of local foods. This study is an experimental study that evaluates the panelists' acceptability of four formulations of plant-based milk with a comparison of different ingredients. The production process includes detoxification, fermentation, and mixing in four formulations, namely P1 (100%:0%), P2 (75%:25%), P3 (50%:50%), and P4 (25%:75%). Organoleptic tests were performed on aroma, taste, and texture attributes using a six-level hedonic scale assessed by 15 untrained panelists. The results showed that the formulation with the dominance of koro sword beans (P4: 25% cassava and 75% sword koro beans) was most preferred in terms of taste and texture, while the best aroma was found in the P3 formulation (50%:50%). Analysis of nutritional content showed that the P2 formulation had the highest carbohydrate content (14.68 mg/g), while the P3 formulation had the highest protein content (7.87 mg/g). This product has the potential to be a nutritious, functional, and sensorially acceptable local plant-based milk.